Pengelolaan Agroforestry Berbasis Kemiri (Aleurites moluccana) dan Pendapatan Petani di Kecamatan Mallawa - Ade Ilham Ismail; Syamsuddin Millang; Makkarennu Makkarennu (Jurnal Hutan dan Masyarakat, 2019)
This study aims to determine the management system, composition and income of candlenut-based agroforestry systems in three villages in the Mallawa District. This research was conducted in May - July 2019 in Batu Putih Village, Tellumpanuae Village, Samaenre Village, Mallawa District. The method used is purposive sampling with respondents, namely farmers who have ≥0.1 ha of land area. The number of plots made was 15 plots to determine the volume of wood and the number of respondents interviewed was 30 to determine the form of management. The data that has been collected is processed and analyzed descriptively and quantitatively. The results showed that the management of coffee-based agroforestry systems was initiated by clearing land from grass or shrubs, followed by spacing, then sources of seedlings obtained from government assistance and planting and maintenance which included weeding, pruning, fertilizing and pest control and diseases which then end with harvesting activities. The average for income in the Batu Putih Village of Rp. 24,372,359 -/ha/year, in the Village of Tellumpanue Rp. 27,875,042, -/ha/year, and the Samaenre Village in the amount of Rp. 22,985,365, -/ha/year.